Contribution and distribution of inorganic ions and organic compounds to the osmotic adjustment in response to salt stress - Zeng, Youling; Li, Ling; Yang, Ruirui; Yi, Xiaoya; Zhang, Baohong (My University, 2015)
The mechanism by which plants cope with salt stress remains poorly understood. The goal of this study is to systematically investigate the contribution and distribution of inorganic ions and organic compounds to the osmotic adjustment (OA) in the halophyte species Halostachys caspica. The results indicate that 100–200 mM NaCl is optimal for plant growth; the water content and degree of succulence of the assimilating branches are higher in this treatment range than that in other treatments; parenchyma cells are more numerous with 100 mM NaCl treatment than they are in control. Inorganic ions (mainly Na+ and Cl-) may play a more important role than organic compounds in NaCl-induced OA and are the primary contributors in OA in H. caspica. The inorganic ions and organic solutes display a tissue-dependent distribution. Na+ and Cl− are accumulated in the reproductive organs and within assimilating branches, which may represent a mechanism for protecting plant growth by way of salt ion dilution and organ abscission. Additionally, OA via increased accumulation of organic substances also protected plant growth and development. This finding provides additional evidence for plant tolerance to salinity stress which can be used for breeding new cultivars for stress tolerance.